Review of Philippe Poirrier (ed.), Pour une histoire des politiques culturelles dans le monde, 1945–2011 [For a history of cultural policies in the world, 1945–2011] - Botsis, Foivos (Historein, 2013)
Review of: Philippe Poirrier (ed.), Pour une histoire des politiques culturelles dans le monde, 1945–2011 [For a history of cultural policies in the world, 1945–2011], La Documentation Française: Paris, 2011. 477 pp.